ANALISIS KINERJA DINAS SOSIAL KOTA PADANG DALAM PENANGGULANGAN BENCANA DI KOTA PADANG (SUATU STUDI MANAJEMEN KEBENCANAAN) - Arief Ivana Putra; Zikri Alhadi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
The research purpose to examine how the performance of the Office of Social Services for disaster management, and the steps taken by the Office of Social Services in disaster management in the City of Padang. This research was carried out at government institutions in the city of Padang, namely the Social Service Office at the Padang city. The research type is descriptive qualitative, file sourced from primary file and secondary file. This file is obtained by interview techniques and documentation. The result of the study indicate that performance of Social Service towards disaster management in Padang City was quite good, but the performance of the Social Service was not optimal. This can be seen from the performance of the Office of Social Affairs which is still experiencing obstacles in terms of facilities, lack of available funds and lack of experience in information technology workers.